Interplay between Jasmonic Acid, Phosphate Signaling and the Regulation of Glycerolipid Homeostasis in Arabidopsis. (8th February 2019) - Chevalier, Florian; Cuyas, Laura; Jouhet, Juliette; Gros, Valrie; Chiarenza, Serge; Secco, David; Whelan, James; Seddiki, Khawla; Block, Maryse A; Nussaume, Laurent; Marechal, Eric
Abstract: Jasmonic acid (JA) biosynthesis and signaling are activated in Arabidopsis cultivated in phosphate (Pi) deprived conditions. This activation occurs mainly in photosynthetic tissues and is less important in roots. In leaves, the enhanced biosynthesis of JA coincides with membrane glycerolipid remodeling triggered by the lack of Pi. We addressed the possible role of JA on the dynamics and magnitude of glycerolipid remodeling in response to Pi deprivation and resupply. Based on combined analyses of gene expression, JA biosynthesis and glycerolipid remodeling in wild-type Arabidopsis and in the coi1-16 mutant, JA signaling seems important in the determination of the basal levels of phosphatidylcholine, phosphatidic acid (PA), monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol. JA impact on MGDG steady state level and fluctuations seem contradictory. In the coi1-16 mutant, the steady state level of MGDG is higher, possibly due to a higher level of PA in the mutant, activating MGD1, and to an increased expression of MGD3 . These results support a possible impact of JA in limiting the overall content of this lipid. Concerning lipid variations, upon Pi deprivation, JA seems rather associated with a specific MGDG increase. Following Pi resupply, whereas the expression of glycerolipid remodeling genes returns to basal level, JA biosynthesis and signaling genes are still upregulated, likely due to a JA-induced positive feedback remaining active. Distinct impacts on enzymes synthesizing MGDG, that is, downregulating MGD3, possibly activating MGD1 expression and limiting the activation of MGD1 via PA, might allow JA playing a role in a sophisticated fine tuning of galactolipid variations.